2014
DOI: 10.1093/ageing/afu073
|View full text |Cite
|
Sign up to set email alerts
|

Identifying patient-level health and social care costs for older adults discharged from acute medical units in England

Abstract: this study highlights the costs accrued by older people discharged from acute medical units (AMUs): they are mainly (76%) in secondary care and half of all costs were incurred by a minority of participants (10%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 5 publications
1
23
1
1
Order By: Relevance
“…Previous studies evaluating health care costs in the elderly evaluate younger elderly populations [5, 8, 14, 15, 18, 33] and few present data disaggregated by age category. In the senior elderly, age-related impairments (e.g., cognitive impairment, falls, fractures) become increasingly important, alongside multiple comorbidities [e.g., cancer, stroke, diabetes mellitus (DM)], but few studies have analyzed coded data for both impairments and morbidities [10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies evaluating health care costs in the elderly evaluate younger elderly populations [5, 8, 14, 15, 18, 33] and few present data disaggregated by age category. In the senior elderly, age-related impairments (e.g., cognitive impairment, falls, fractures) become increasingly important, alongside multiple comorbidities [e.g., cancer, stroke, diabetes mellitus (DM)], but few studies have analyzed coded data for both impairments and morbidities [10].…”
Section: Introductionmentioning
confidence: 99%
“…Raw data extraction can be problematic, particularly in primary care [6]. For large studies, such as PLEASANT (with 108 practices with 12 months of data and 8190 patients), using CPRD may be considered an efficient approach, particularly given that CPRD data are relatively readily available, it is possible to plan study time horizons with expected extraction times, and a data dictionary is available to assess data availability against the needs of the study.…”
Section: Discussionmentioning
confidence: 99%
“…The logistical benefits of using large databases may be desirable for researchers, funding bodies looking for studies that use efficient designs and the National Health Services (NHSs) within the United Kingdom (UK) in general; such study designs have been suggested as an approach to enable patients to be entered into RCTs more quickly than traditional study designs [4]. The accurate measurement of patient-level resource-use information for the purpose of economic evaluation has historically been challenging when relying on self-reported methods [5] or raw data extracted from healthcare services [68]. These large observational databases provide a great deal of patient-level resource-use information, which includes data about doctors’ visits in clinic or at home, inpatient or outpatient care and prescribed drugs at the practice level—the type of data available depends on the database.…”
Section: Introductionmentioning
confidence: 99%
“…Such data could be used for service evaluations, albeit with a variety of time, monetary, technical and information governance restrictions [68]. As such, routine data are recommended but often difficult to utilise [28,68,75].…”
Section: Routine Data For Estimating Resource Use Costs and Non-monementioning
confidence: 99%